Indigenous Pest Management: Scientific Validity or Folklore? - Karki, Rojan; Giri, Koshila; Pokhrel, Urmila (Nepalese Journal of Agricultural Sciences, 2025)
Traditional pest management practices, deeply rooted in Nepal’s indigenous knowledge and cultural heritage, have played a significant role in the country’s agricultural systems for generations. While many of these methods are based on oral traditions and anecdotal evidence, a number have been scientifically validated and align well with the principles of sustainable agriculture. This review critically explores various native pest control techniques, evaluating their effectiveness and relevance in the modern context. It underscores the potential of integrating traditional wisdom with scientific innovation to develop environmentally sound and culturally respectful pest management strategies. The findings emphasize the importance of further research and supportive policies to incorporate proven traditional methods into contemporary agricultural frameworks.